Mini‐Generator Based on Reciprocating Vertical Motions Driven by Intracorporeal Energy. Issue 8 (12th March 2019) - Zhang, Lina; Cheng, Mengjiao; Luo, He; Zhang, Haibo; Ju, Guannan; Liu, Peng; Zhou, Yifeng; Shi, Feng
Abstract: Most implantable devices rely on a power supply from batteries and require replacement surgeries once the batteries run low. Mini‐generators that harvest intracorporeal energy available in the human body are promising replacements of batteries and prolong the lifetime of implantable devices, thus reducing surgery pain, risks, and cost. Although various sources of energy available in the human body are used for electricity generation using piezoelectric and triboelectric materials or intravascular turbines, concerns about material durability or thrombus risks remain, and developing novel strategies to fabricate a mini‐generator to harvest the intracorporeal energy is still challenging. Herein, a mini‐generator system is designed by exporting the systolic/diastolic blood pressure from the femoral artery of a sheep to trigger the pressure‐responsive reciprocating vertical motions of a conductor. By applying a magnetic field, an induced voltage of 0.32 V and a stable output power of 13.86 µW are obtained, which is promising to power a state‐of‐the‐art pacemaker (8–10 µW). The noncontact electricity generation strategy provides a novel avenue to sustainable power supply for implantable devices. Abstract : A mini‐generator harvesting intracorporeal energy in the bloodstream is demonstrated. By exporting the systolic/diastolic blood pressure of a sheep as a trigger, a stable output of 13.86 µW is obtained through the pressure‐responsive reciprocating vertical motions of a conductor in a magnetic field. Noncontact electricity generation out of blood vessels is a promising method to power implantable devices.